Dielectric properties of graphene–iron oxide/polyimide films with oriented graphene. Issue 12 (26th November 2015) - Ding, Ling; Liu, Leipeng; Li, Penggang; Lv, Fengzhu; Tong, Wangshu; Zhang, Yihe
ABSTRACT: The preparation of high‐dielectric‐constant ( k ) materials is important in the field of electronics. However, how to effectively use the function of fillers to enhance k is still a challenge. In this study, anisotropic graphene (GNS)–iron oxide (Fe3 O4 )/polyimide (PI) nanocomposite films with oriented GNSs were prepared by the in situ polymerization of 4, 4′‐oxydianiline and pyromellitic anhydride in the presence of GNS–Fe3 O4 . Films of the precursors were fabricated, and this was followed by stepwise imidization under a magnetic field at a higher temperature to orient the magnetic sheets. The orientation of GNS–Fe3 O4 and the relationships of the GNS–Fe3 O4 content and measurement frequency with the dielectric properties of the GNS–Fe3 O4 /PI films were studied in detail. The dielectric property differences of the GNS–Fe3 O4 /PIs with GNS–Fe3 O4 parallel or perpendicular to the film surface were not obvious, when the content of GNS–Fe3 O4 was lower than 5 wt %. However, at the percolation threshold, the k values of GNS–Fe3 O4 /PI films with horizontal GNS–Fe3 O4 were much higher than those of the other two kinds of films at 10 3 Hz; this was derived from the contribution of more effective microcapcitors parallel to the film surface. So, making the GNS–Fe3 O4 parallel to the film surface greatly enhanced k of GNS–Fe3 O4 . However, switching the charges on the large lateral surface of the parallel GNSs with the electric field also caused a higher dielectric loss and the frequency dependence of k and the dielectric loss at low frequency. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43041. Abstract :